Генетичні основи селекції на розширення різновиднісного різноманіття ячменю ярого - Козаченко, М.Р.; Солонечний, П.М. (Фактори експериментальної еволюції організмів, 2013)
Aims. The establishment of genetical peculiarities and efficiency of the application of the traits in rare variatal forms during breeding and widening of a varietal diversity in spring barley on its basis. Methods. Genetical-breeding methods are used: they are field (diallel crossing, phenology, heretability of plant traits); genetical-statistical (dispersion, variegated, correlation, genetical). Results. Some distinctions as to morpho-biological peculiarities, variability, correlation, inheritance, components of genetical dispersion, heritability, combining ability and a breeding value of traits in the forms of rarely- and widely used varieties of spring barley are established. The varietal diversity of the sources of valuable traits is widened. Conclusions. The genetical peculiarities for the creation of a new genetical diversity of various varietal forms of spring barley are established.

Key words: spring barley, variety, diallel crosses, genetical specific, breeding.